(untitled) (Journal of Hama University, 2026)
Due to the huge increase in its quantities and the absence of effective management of them, especially in developing countries Construction and demolition waste is a source of great concern to researchers in the world,. It has become a large proportion of solid waste as a result of urban development on the one hand, and wars and devastating disasters on the other. In this study, attention was directed towards the problem of accumulation of construction and demolition waste, and the study suggested choosing a site to establish a stationary station for the collection and sorting of this waste instead of dumping it in random landfills and construction sites to make optimal use of it. Eight criteria were adopted (population agglomerations, archaeological and tourist centers, vegetation, direction of mountain slopes and prevailing winds, rivers, main road network, Mediterranean coast, land inclination or slope). These criteria were selected and weighted using the multi-criteria decision analysis technique (MCDA). Specifically, the analysis hierarchical process (AHP), with the help of (5) five expert opinions and similar studies. This technology was integrated with geographic information systems (GIS) to study the suitability of the land to locate a waste collection and sorting (C&D) center. It was found from the expert opinions that the environmental criteria is the most important in determining the location of the C&D waste management center in Lattakia.